Answer:
The line of the equation in the point-slope form of the line passing through the point (3, -1) and having slope 1/2 will be:
![y +1 = \frac{1}{2} (x-3)](https://tex.z-dn.net/?f=y%20%2B1%20%3D%20%5Cfrac%7B1%7D%7B2%7D%20%28x-3%29)
Please check the attached graph.
Step-by-step explanation:
Given
<u>Point slope form:</u>
![y-y_1=m\left(x-x_1\right)](https://tex.z-dn.net/?f=y-y_1%3Dm%5Cleft%28x-x_1%5Cright%29)
where
- m is the slope of the line
In our case:
m = 1/2
The point (x₁, y₁) = (3, -1)
substituting the values m = 1/2 and the point (x₁, y₁) = (3, -1) in the point-slope form of the line equation
![y-y_1=m\left(x-x_1\right)](https://tex.z-dn.net/?f=y-y_1%3Dm%5Cleft%28x-x_1%5Cright%29)
![y - (-1) = \frac{1}{2} (x-3)](https://tex.z-dn.net/?f=y%20-%20%28-1%29%20%3D%20%5Cfrac%7B1%7D%7B2%7D%20%28x-3%29)
![y +1 = \frac{1}{2} (x-3)](https://tex.z-dn.net/?f=y%20%2B1%20%3D%20%5Cfrac%7B1%7D%7B2%7D%20%28x-3%29)
Thus, the line of the equation in the point-slope form of the line passing through the point (3, -1) and having slope 1/2 will be:
![y +1 = \frac{1}{2} (x-3)](https://tex.z-dn.net/?f=y%20%2B1%20%3D%20%5Cfrac%7B1%7D%7B2%7D%20%28x-3%29)
Please check the attached graph.